Surface interactions and viability of coronaviruses. Issue 174 (27th January 2021) - Aydogdu, Mehmet Onur; Altun, Esra; Chung, Etelka; Ren, Guogang; Homer-Vanniasinkam, Shervanthi; Chen, Biqiong; Edirisinghe, Mohan
Abstract : The recently emerged coronavirus pandemic (COVID-19) has become a worldwide threat affecting millions of people, causing respiratory system related problems that can end up with extremely serious consequences. As the infection rate rises significantly and this is followed by a dramatic increase in mortality, the whole world is struggling to accommodate change and is trying to adapt to new conditions. While a significant amount of effort is focused on developing a vaccine in order to make a game-changing anti-COVID-19 breakthrough, novel coronavirus (SARS-CoV-2) is also developing mutations rapidly as it transmits just like any other virus and there is always a substantial chance of the invented antibodies becoming ineffective as a function of time, thus failing to inhibit virus-to-cell binding efficiency as the spiked protein keeps evolving. Hence, controlling the transmission of the virus is crucial. Therefore, this review summarizes the viability of coronaviruses on inanimate surfaces under different conditions while addressing the current state of known chemical disinfectants for deactivation of the coronaviruses. The review attempts to bring together a wide spectrum of surface–virus–cleaning agent interactions to help identify material selection for inanimate surfaces that have frequent human contact and cleaning procedures for effective prevention of COVID-19 transmission.